Radical Criminology: A Sympathetic Criticism from the Viewpoints of Philosophical and Theological Anarchism - Watkins, J. Anthony (1979)
The point of departure for this work is to sympathetically critique American radical criminology from an anarchist philosophical and theological viewpoint. Most criticism of radical criminology has thus far come from politically conventional and orthodox Marxist sources. Anarchism is to the left of Marxism or scientific socialism and has been characteristically left of conservatism and liberalism. By sympathetic critique what is meant is that this author tends to favor and support most of the criticism radical criminology has levelled against conventional criminology. However, radical criminology is apparently unwilling to critically comprehend its own essentially anarcho-religious, rather than authentically Marxist character. Thus, the criticism herein is mainly to assist radical criminology in its search for a Weltanschauung which best fits its purposes and ends